Continuous Dependence in Front Propagation for Convective Reaction-Diffusion Models with Aggregative Movements - Luisa Malaguti; Cristina Marcelli; Serena Matucci (Abstract and Applied Analysis)
The paper deals with a degenerate reaction-diffusion equation, including aggregative movements and convective terms. The model also incorporates a real parameter causing the change from a purely diffusive to a diffusive-aggregative and to a purely aggregative regime. Existence and qualitative properties of traveling wave solutions are investigated, and estimates of their threshold speeds are furnished. Further, the continuous dependence of the threshold wave speed and of the wave profiles on a real parameter is studied, both when the process maintains its diffusion-aggregation nature and when it switches from it to another regime.